Analytical protocol for measuring micro-molar quantities of sulfur volatile species in experimental high pressure and temperature fluids - Arianna Secchiari; Luca Toffolo; Sandro Recchia; Simone Tumiati (Communications Chemistry)
Abstract Validating thermodynamic models is essential in experimental geosciences for exploring increasingly complex systems and developing analytical protocols. However, investigating solid–fluid equilibria in mm3-sized experimental capsules poses several challenges, particularly in sulfur-bearing chemical systems. These include maintaining bulk fluid composition and performing quantitative analysis with extremely low amounts of synthesized fluid. We present an innovative methodology for measuring ultra-low amounts of sulfur volatiles (H2S and SO2) generated during experimental runs at high pressure and temperature conditions of 3 GPa and 700 °C. Using solid sulfides (FeS + FeS2) and water as reactants, we performed redox-controlled syntheses employing a piston cylinder apparatus. We demonstrate that ex-situ measurements of these fluids by quadrupole mass spectrometry ensure accurate and precise analysis, confirming predicted thermodynamic compositions. This methodology allows in-depht investigation of sulfide solid–fluid equilibria, shedding light on sulfur volatiles behavior and geochemical cycles under high P–T conditions characteristic of the Earth’s interior.